Desenvolvimento de ferramentas moleculares para elucidação de mecanismos de ajustes fisiológicos do pacu submetido a jejum - Squassoni, Gustavo Henrique [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Brazilian aquaculture is as a commercial activity on the rise. Among the native species, pacu, Piaractus mesopotamicus, stands out as one of the most reared in the southern, central and northeastern Brazil. However, similar to what occurs with other commercial species, the production of pacu experience problems during the production process, such as high population density used, incorrect food supply and stress, resulting in reduced productivity and increased mortality. One of the strategies investigated to improve the management of fish feeding is the use of dietary restrictions for a certain time to promote growth compensation during the refeeding period. However, information related to physiological responses and cell modulations caused by this type of management are still unknown. Understanding this information is necessary for the development of strategies to minimize the stress caused by food restriction. The purpose of this study was to evaluate the impact of prolonged fasting, followed by short refeeding on the physiological parameters, gene expression related to growth and stress, the prevalence of certain bacterial groups in the mucosa and intestinal content and cloning, identification and validation of reference genes for normalization of gene expression data in studies with pacu. The results showed that the pacu has great capacity for mobilization of endogenous reserves, but their recovery is faster in smaller fish. This study presents the first experimental comparisons for validation of reference genes for pacu. Cloned, sequenced and validated genes will be used in future studies of gene expression with this species. In addition, this study provides the first information about the changes in intestinal microbiota in pacu. The use of qPCR for the detection and quantification of specific bacterial groups proved to be an important tool for assessing changes in bacterial communities in the mucosa and intestinal contents of fish

A aquicultura brasileira apresenta-se como atividade comercial em franca ascensão e, dentre as espécies nativas, o pacu, Piaractus mesopotamicus, destaca-se como uma das mais cultivadas nas regiões Sul, Sudeste e Centro Oeste do Brasil. Contudo, à semelhança do que ocorre com as demais espécies de interesse comercial, a produção do pacu enfrenta problemas ao longo do processo produtivo, tais como a alta densidade populacional utilizada, fornecimento incorreto de rações e estresse, que resultam em redução da produtividade e aumento na taxa de mortalidade. Uma das estratégias estudadas para melhorar o manejo alimentar em peixes consiste na utilização da privação alimentar por tempo determinado com a finalidade de promover compensação do crescimento, durante o período de realimentação. Entretanto, informações relacionadas às respostas fisiológicas, de modulação celular e de possíveis alterações na microbiota intestinal provocada por este tipo de manejo ainda são discordantes. A compreensão destas informações é necessária para o desenvolvimento de estratégias que minimizem o estresse ocasionado pela privação alimentar. Diante do exposto, a proposta deste trabalho foi avaliar o impacto do jejum prolongado, seguido de curto período de realimentação, sobre os parâmetros fisiológicos, expressão de genes relacionados ao processo de crescimento e estresse, prevalência de determinados grupos bacterianos na mucosa e conteúdo intestinal, além da clonagem, identificação e validação de genes de referência para normalização de dados de expressão gênica em estudos com pacus. Os resultados obtidos demonstraram que o pacu apresenta grande capacidade de mobilização das reservas endógenas, porém a recuperação das mesmas é mais rápida em peixes de menor tamanho. O presente estudo apresenta as primeiras comparações experimentais para validação de genes de referência para o pacu. Os genes clonados...
Keywords: Peixe; Pacu (Peixe); Jejum; Peixe - Fisiologia; Microbiota; Fishes Physiology